Ablation of gut microbiota alleviates obesity-induced hepatic steatosis and glucose intolerance by modulating bile acid metabolism in hamsters - Lulu Sun; Yuanyuan Pang; Xuemei Wang; Qing Wu; Huiying Liu; Bo Liu; George Liu; Min Ye; Wei Kong; Changtao Jiang (Elsevier, 2019)
Since metabolic process differs between humans and mice, studies were performed in hamsters, which are generally considered to be a more appropriate animal model for studies of obesity-related metabolic disorders. The modulation of gut microbiota, bile acids and the farnesoid X receptor (FXR) axis is correlated with obesity-induced insulin resistance and hepatic steatosis in mice. However, the interactions among the gut microbiota, bile acids and FXR in metabolic disorders remained largely unexplored in hamsters. In the current study, hamsters fed a 60% high-fat diet (HFD) were administered vehicle or an antibiotic cocktail by gavage twice a week for four weeks. Antibiotic treatment alleviated HFD-induced glucose intolerance, hepatic steatosis and inflammation accompanied with decreased hepatic lipogenesis and elevated thermogenesis in subcutaneous white adipose tissue (sWAT). In the livers of antibiotic-treated hamsters, cytochrome P450 family 7 subfamily B member 1 (CYP7B1) in the alternative bile acid synthesis pathway was upregulated, contributing to a more hydrophilic bile acid profile with increased tauro-β-muricholic acid (TβMCA). The intestinal FXR signaling was suppressed but remained unchanged in the liver. This study is of potential translational significance in determining the role of gut microbiota-mediated bile acid metabolism in modulating diet-induced glucose intolerance and hepatic steatosis in the hamster. KEY WORDS: Gut microbiota, CYP7B1, TβMCA, FXR, Metabolic disorders